ESG Disclosure and Capital Structure on Financial Performance: The Moderating Role of Firm Size in Indonesian State-Owned Enterprises and Mining Companies - Syafaat, Farid Azhar; Setyaningsih, Nina Dwi (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study aims to analyze the effect of ESG disclosure and capital structure on financial performance with firm size as a moderating variable in state-owned enterprises and mining sector companies listed on the Indonesia Stock Exchange during 2022–2024. Secondary data from 39 companies with 117 observations were analyzed using panel data regression with Random Effect Model (REM) and Moderated Regression Analysis (MRA) approaches. The results demonstrate that ESG disclosure has no significant effect on financial performance, reflecting that Indonesia's capital market has not fully incorporated sustainability values into short-term profitability assessments. Capital structure proved to have a negative and significant effect on financial performance, indicating that excessive debt dependency suppresses asset management efficiency. Firm size failed to moderate the influence of both independent variables on financial performance. These findings affirm that prudent financing structure management is more decisive in determining profitability than the extent of sustainability disclosure alone.